Validation of a DNA methylation HPV triage classifier in a screening sample. Issue 11 (8th February 2016) - Lorincz, Attila T.; Brentnall, Adam R.; Scibior‐Bentkowska, Dorota; Reuter, Caroline; Banwait, Rawinder; Cadman, Louise; Austin, Janet; Cuzick, Jack; Vasiljević, Natasa
Abstract : High‐risk human papillomavirus (hrHPV) DNA tests have excellent sensitivity for detection of cervical intraepithelial neoplasia 2 or higher (CIN2+). A drawback of hrHPV screening, however, is modest specificity. Therefore, hrHPV‐positive women might need triage to reduce adverse events and costs associated with unnecessary colposcopy. We compared the performance of HPV16/18 genotyping with a predefined DNA methylation triage test (S5) based on target regions of the human gene EPB41L3, and viral late gene regions of HPV16, HPV18, HPV31 and HPV33. Assays were run using exfoliated cervical specimens from 710 women attending routine screening, of whom 38 were diagnosed with CIN2+ within a year after triage to colposcopy based on cytology and 341 were hrHPV positive. Sensitivity and specificity of the investigated triage methods were compared by McNemar's test. At the predefined cutoff, S5 showed better sensitivity than HPV16/18 genotyping (74% vs 54%, P = 0.04) in identifying CIN2+ in hrHPV‐positive women, and similar specificity (65% vs 71%, P = 0.07). When the S5 cutoff was altered to allow equal sensitivity to that of genotyping, a significantly higher specificity of 91% was reached ( P < 0.0001). Thus, a DNA methylation test for the triage of hrHPV‐positive women on original screening specimens might be a valid approach with better performance than genotyping. Abstract : What's new? DNA testing for high‐risk human papillomaviruses (hrHPVs) can both detect and predict the development of precancerous cervical lesions. Limitations in specificity, however, necessitate the generation of triage strategies to minimize unneeded colposcopy among hrHPV‐positive women. According to this study, triage may be readily affected using a DNA methylation classifier based on the human gene EPB41L3 and the late gene regions of HPV16, HPV18, HPV31 and HPV33. The devised classifier outperformed triage by HPV16/18 genotyping in a cohort of hrHPV‐positive patients. The strategy could fill a key role in hrHPV triage in cervical screening programs.